Denaturing HPLC for Identifying Bacteria. (August 2002) - Hurtle, William; Shoemaker, David; Henchal, Erik; Norwood, David
Denaturing HPLC (DHPLC) is used in a wide variety of genetic applications. Here we introduce a new application for this technique, the identification of bacteria. We combined the capability of DHPLC to detect sequence variation with the principles of rRNA genotyping analysis to develop a high-throughput method of identifying microorganisms. Thirty-nine bacterial species from a broad spectrum of genera were tested to determine if DHPLC could be used for identification. Most (36 of 39) species of bacteria had a unique peak profile that could be used as a molecular fingerprint. Furthermore, a blind panel of 65 different bacterial isolates was analyzed to demonstrate the diagnostic capability of this method to specifically identify Yersinia pestis and Bacillus anthracis . All the Y. pestis samples (10 of 10) and the majority of B. anthracis samples (12 of 14) were correctly identified. The procedure had an overall specificity of 100%, overall sensitivity of 91.7%, and a predictive value of 96.9%. The data suggest that DHPLC of products spanning regions of genetic variability will be a useful application for bacterial identification.